2021
DOI: 10.1002/cav.2013
|View full text |Cite
|
Sign up to set email alerts
|

Learning‐based pose edition for efficient and interactive design

Abstract: Authoring an appealing animation for a virtual character is a challenging task. In computer-aided keyframe animation artists define the key poses of a character by manipulating its underlying skeletons. To look plausible, a character pose must respect many ill-defined constraints, and so the resulting realism greatly depends on the animator's skill and knowledge. Animation software provide tools to help in this matter, relying on various algorithms to automatically enforce some of these constraints. The increa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Recently, Victor et al [2021] introduce an IK solver that is based on an autoencoder structure, which aligns hand joints to the target position from a starting pose. However, their model has some limitations as it modifies the entire skeleton each time an end-effector is altered, resulting in the emergence of foot-sliding artifacts and a lack of temporal coherence.…”
Section: Learned Inverse Kinematicsmentioning
confidence: 99%
“…Recently, Victor et al [2021] introduce an IK solver that is based on an autoencoder structure, which aligns hand joints to the target position from a starting pose. However, their model has some limitations as it modifies the entire skeleton each time an end-effector is altered, resulting in the emergence of foot-sliding artifacts and a lack of temporal coherence.…”
Section: Learned Inverse Kinematicsmentioning
confidence: 99%
“…Animation courses utilize both online and offline hybrid teaching methods to make full use of afterschool time and expand students' access to knowledge [15]. Léon Victor et al In computer-assisted keyframe animation, the designer defines the character's key poses by manipulating the character's underlying skeleton to make it vividly rendered according to the scripted content, which is used for the explanation of the character in the later stage of Motion Graphics (MG) [16]. Noetel, M. et al argued that testing the effect of multimedia art design on learning or cognitive load found that multimedia art enables students to learn professional techniques subtly and cultivates the awareness of students to be actively informed of the new concepts, techniques and methods in the industry positions, so as to achieve the purpose of improving their own professional and business level [17].…”
Section: Introductionmentioning
confidence: 99%